Atrial Flutter in a Newborn: A Case Report - Reza Saeidi; Ezzat Khodashenas; Rana Tafrishi; Farnaz Mousavi; Alireza Sohrabi (Mashhad University of Medical Sciences, 2023)
Background: Arrhythmia detection in neonates is substantially different from that in older children. The natural history of arrhythmias in the neonatal age group also differs markedly from other ages. Neonatal Cardiac Arrhythmias are found in 1% to 5% of newborns during the first 10 days of life. Most are premature supraventricular tachycardia (SVT) beats that will disappear over the first month of life. The most common symptomatic arrhythmia in the neonatal period is SVT, which has an incidence of 1/25,000. Idiopathic neonatal atrial flutter (AFL) is a rare rhythm disorder usually occurring in the first days of life and characterized by sustained tachycardia in newborns and infants with an atrial rate of often at around 340-580 beats/min. AFL may manifest as asymptomatic tachycardia, congestive heart failure, or hydrops and may be life-threatening and fatal.Case report: We reported a 38-weak-female baby presented with tachycardia during the first physical examination. The patient underwent adenosine therapy twice, and when the electrocardiogram demonstrated atrial flutter, the next choice was cardioversion. After using cardioversion with a dose of 2 J, the rhythm converted to the normal sinus and the following clinical and laboratory tests showed no abnormality. With early prenatal diagnosis and prompt therapeutic approaches, most of the patients showed good prognosis and there was no need for chronic therapy.Conclusion: Since AFL may result in severe heart failure and even death, it should be noted that careful clinical examination and on-time diagnosis of cardiac arrhythmia are of significant importance.